Figurative Language as Reflected in Worthsworth’s Resolution and Independence - Tini Mogea; Salaki Reynaldo Joshua (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
The purpose of this study is to reveal the figurative language in William Wordsworth’s Resolution and Independence. The writer used qualitative research because the data collected were in the form of words. The objective and expressive approaches were used in analyzing the data. The writer finds that figurative language is used in Resolution and Independence such as personification, metaphor, simile, and symbol. The peculiar the objects of nature such as sky, mist, cloud, stone, and rock, and also animals such as hares, and sea-beast, incorporated with the natural phenomena have become the primary objects of these figurative languages. The poem is an overflow of Wordsworth’s emotion that transforms through the object of nature and the natural phenomena. In order words, Wordsworth is projecting his own feelings and emotion into the object, and the natural phenomena